Hydrogeological characterization of the aquifer system located in the communities of Isla Chica and La Trocha, Los Chiles, Alajuela - Vargas, Rigoberto (2025)
This research focuses on the hydrogeological characterization of the aquifer system in the Isla Chica and La Trocha communities. This system corresponds to a transboundary aquifer within the San Juan River basin (Costa Rica-Nicaragua). It is important to note that the groundwater is used by the local residents and migrants who live itinerantly in these areas. In addition, there are very few studies of this nature conducted in the region. This work identifies the presence of two aquifers: the first is a shallow, unconfined aquifer covered by a clay layer, with low transmissivity, consisting of intercalated layers of sand and clay that are captured through hand-dug wells. The second is a deeper, semi-confined aquifer, with an average thickness of 40 m, composed of volcaniclastic sands. This aquifer is exploited through drilled wells. The static level recorded for the drilled wells may reflect an equilibrium level between aquifers, typically ranging from 10 to 30 m deep. The deeper aquifer is overlain by a poorly permeable reddish clay layer with an average thickness of 30 m. The groundwater flow direction is from South to North, toward the San Juan River. Hydrogeochemically, the mixed water is classified as calcium bicarbonate. According to the GOD model, the vulnerability of the shallow aquifer to contamination is low to medium. The potential recharge, calculated using the method proposed by Schosinsky (2006), is estimated to be between 357.82 mm and 491.70 mm per year.